A DOLBEAULT ISOMORPHISM FOR COMPLETE INTERSECTIONS IN INFINITE-DIMENSIONAL PROJECTIVE SPACE - Kotzev, Boris (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2005)
We consider a complex submanifold $X$ of finite codimension in an infinite-dimensional complex projective space $P$ and a holomorphic vector bundle E over X. Given a covering $\mathcal{U}$ of X with Zariski open sets, we define a subcomplex $\mathcal{C}(X, E)$ of the Čech complex corresponding to the vector bundle E and the covering $\mathcal{U}$. For a special class of coverings $\mathcal{U}$, we prove that the complex $\mathcal{C}(X, E)$ is acyclic when X is a complete intersection and P admits smooth partitions of unity.